Technology Readiness Index in The Application of Blockchain Technology In Indonesian Carbon Exchange - Dayan Hakim Natigor Sipahutar; Yoyo Sudaryo; Taufik Walhidayat; Gary Cokins (Politeknik APP Jakarta, 2024)
The integration of Information and Communication Technology (ICT) with Blockchain technology has indeed brought about significant changes across various aspects of digital economic activities. This study provides a perspective on the influence of blockchain use on the performance of Indonesian Carbon Exchange players. The results of data analysis show that the variables Optimism (p-value 0.001<0.05) and Innovation (p-value 0.000<0.05) in the adoption of blockchain technology have a significant positive influence on the performance of Indonesian Carbon Exchange players. The results of testing the Insecurity variable on social media adoption showed significant negative results with a p-value of 0.002 (<0.05). And the results of testing the Discomfort variable with the adoption of blockchain technology have no influence on the performance of Indonesian Carbon Exchange players with a p-value of 0.074 (>0.05).